2023
DOI: 10.1021/acsami.3c06908
|View full text |Cite
|
Sign up to set email alerts
|

Electrolysis Process-Facilitated Engineering of Primary Particles of Cobalt-Free LiNiO2 for Improved Electrochemical Performance

Abstract: The particle morphology of LiNiO 2 (LNO), the final product of Co-free high-Ni layered oxide cathode materials, must be engineered to prevent the degradation of electrochemical performance caused by the H2−H3 phase transition. Introducing a small amount of dopant oxides (Nb 2 O 5 as an example) during the electrolysis synthesis of the Ni(OH) 2 precursor facilitates the engineering of the primary particles of LNO, which is quick, simple, and inexpensive. In addition to the low concentration of Nb that entered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Besides, the XPS results (Figure S16 ), 51 O 1s (M−O, ROLi, C�O, C−O, Li x PF y O 2 ), 52 F 1s (LiF, Li x PF y O 2 / Li x PF y ), 53 and P 2p (Li x PF y O 2 , Li x PF y ). 54,55 By fitting the XPS results, it can be indicated that the Zr gradient doping samples have a higher surface stability. After long cycling, the peak of M−O (529.4 eV) can be detected in the O 1s of 10Zr PFCG, while other samples do not show this peak, implying that the impurity on 10Zr PFCG is much less than that on 10Zr NFCG and bare FCG, which will decelerate the capacity degradation.…”
Section: Mechanismmentioning
confidence: 99%
“…Besides, the XPS results (Figure S16 ), 51 O 1s (M−O, ROLi, C�O, C−O, Li x PF y O 2 ), 52 F 1s (LiF, Li x PF y O 2 / Li x PF y ), 53 and P 2p (Li x PF y O 2 , Li x PF y ). 54,55 By fitting the XPS results, it can be indicated that the Zr gradient doping samples have a higher surface stability. After long cycling, the peak of M−O (529.4 eV) can be detected in the O 1s of 10Zr PFCG, while other samples do not show this peak, implying that the impurity on 10Zr PFCG is much less than that on 10Zr NFCG and bare FCG, which will decelerate the capacity degradation.…”
Section: Mechanismmentioning
confidence: 99%